Very little intron loss/gain in Plasmodium: Intron loss/gain mutation rates and intron number - Roy, Scott William; Hartl, Daniel L.

(untitled) (Genome Research, 2006)
We compared intron positions in conserved regions of 3479 orthologous gene pairs from Plasmodium falciparum and Plasmodium yoelii, which likely diverged ≥100 million years ago (Mya). Only 27 out of 2212 positions were specific to one of the two species. Intron presence in related species shows that at least 19 and possibly 26 of the changes are due to intron loss, depending on phylogeny. The implied intron loss and gain rates are much lower than previously estimated for nematodes, arthropods, fungi, and plants, and are comparable only with the rates in vertebrates. That all observed changes were exact, occurring without loss or gain of flanking coding sequence, suggests intron loss via an mRNA intermediate, as does a nonsignificant trend toward loss of introns at adjacent positions. Many of the intron changes occurred in genes encoding proteins involved in nucleic acid-related processes, as previously found for intron gains in nematodes. Two changes occurred in the chloroquine resistance transporter, suggesting a role for positive selection in intron loss in Plasmodium. The dearth of intron loss and gain could be explained by the lack of known transposable elements in Plasmodium, since transposable elements and/or reverse transcriptase are thought to be necessary for both processes. The observed pattern suggests that the availability of stochastic intron loss and gain mutations can be a major determinant of changes in intron number.